Cambios en los períodos fundamentales de edificaciones construidas con el gran panel soviético - Yamila Concepción Socarrás Cordoví (Universidad de Cuenca, 2021)
After a visual inspection of 200 buildings built with the prefabricated great soviet panel system in Santiago the Cuba, factors leading to potential seismic damage were detected. These factors include pathological damage to structural elements and joints, with severe levels of damage. Likewise, changes in weight and / or rigidity, due to the violations of the residents. In order to forecast the seismic behavior of these buildings, the fundamental period is determined in 7 of them through environmental vibrations. Then, with these results, using linear analysis methods, the models of the buildings are calibrated. In the calibration, flexural stiffness modifiers are iteratively incorporated into the structural models. In addition, the properties of the materials are taken into account based on the results of destructive and non-destructive tests on concrete and steel. Both by instrumental and analytical means, similar values of the fundamental periods of oscillation are reached when faced with the earthquake of calculation. Changes in the seismic behavior of these buildings are envisaged as a result of increases in the fundamental periods of oscillation and the coupling of the oscillations.